Cardiovascular risk, renal hypertensive damage, and effects of amlodipine treatment in transgenic TGR(mREN2)27 rats - Witte, Klaus; Schnecko, Anke; Schmidt, T.; Voll, Christian; Kränzlin, Bettina; Lemmer, Björn (General pharmacology, 1999)
Transgenic rats (TGRs) TGR(mREN2)27 are characterized by fulminant hypertension, an inverse circadian blood pressure rhythm, and severe hypertensive target organ damage. In the present study, we evaluated cardiovascular risk factors, renal function, and urinary protein loss in transgenic rats before and after treatment with the calcium channel blocker amlodipine. Amlodipine was injected intraperitoneally in a dose of 5 mg/kg/day, either once daily at 8.00 h or twice daily in divided doses at 8.00 and 20.00 h. Untreated TGRs and Sprague-Dawley rats served as hypertensive and normotensive controls, respectively. Before and after 5 weeks of treatment, rats were placed in metabolic cages for sampling of urine. Prior to treatment, urinary excretion rates of protein, albumin, and Ca2+ were significantly higher in TGRs than in Sprague-Dawley controls. Urinary excretion of protein and albumin was reduced by 5 weeks of amlodipine treatment, whereas the excretion of Ca2+ was not affected. The reductions in renal proteinuria and albuminuria by amlodipine treatment were significantly correlated with the treatment-induced decrease in blood pressure. These findings indicate that blood pressure itself is an important contributor to albumin loss by the kidney in renin-dependent hypertension of TGRs.